Posyandu Cadres: stunting frontliners – innovative IEC training at Perumnas II Health Center, Pontianak - Zakiyya, Affi; Pangestu, Jehani Fajar; Aristia, Eriza (Poltekkes Kemenkes Bandung, 2025)
Stunting, a consequence of chronic malnutrition during the first 1000 days of life, significantly impedes child growth and development. Indonesia continues to face a high prevalence of stunting, including an increase in cases within the working area of Perumnas II Community Health Center in Pontianak. Given the crucial role of Posyandu cadres in the early detection and education regarding both growth and developmental aspects of stunting, strengthening their Communication, Information, and Education (CIE) capabilities becomes an urgent priority to support optimal toddler development at the community level. This community service activity aimed to enhance cadres' CIE skills in detecting developmental delays in stunted toddlers, foster closer cross-sectoral collaboration, and prepare adequate resources for more effective stunting management at the community level. The methodology employed a participatory and educational approach through a series of activities. The results of this activity demonstrated a significant increase in Posyandu cadres' knowledge of CIE for stimulating stunted toddler development following the training. Cadres were able to effectively utilize CIE techniques and media in disseminating information to the community. In conclusion, this community service project effectively improved Posyandu cadres' knowledge and skills in conveying information about stimulating stunted toddler development, thereby empowering them to play a more active role in stunting prevention efforts at the community level.